Prophylactic botulinum type A toxin complex (Dysport®) for migraine without aura - Chankrachang S. (2014)
Objective.-To evaluate the efficacy, safety, and optimum dose of a highly purified Clostridium botulinum type A toxin-hemagglutinin complex (Dysport) for migraine prophylaxis. Background.-Botulinum toxin type-A has demonstrated good efficacy in several open-label studies of patients with migraine, involving either individualized or standardized protocols, although data from placebo-controlled trials have been conflicting. Methods.-A 12-week, double-blind, randomized trial of Dysport (120 or 240 units) vs placebo was conducted in 6 centers in Thailand to evaluate the efficacy, safety, and optimum dose of botulinum toxin type-A (Dysport) for migraine prophylaxis. A total of 128 patients with migraine without aura were enrolled. The primary end point was the change in the mean number of migraine attacks per 4-week period from the pre-treatment period to 8-12 weeks post injection. Secondary efficacy measures included the change in the mean total intensity score from the pre-treatment period to 8-12 weeks, the investigator and patient global assessments of change at each visit compared with pre-treatment, and Migraine Disability Assessment and Short Form-36 scores. Results.-Change in number of migraine attacks from pre-treatment to weeks 8-12 was not significantly different. There was a greater improvement in total intensity score at weeks 8-12 with Dysport-240 (not significant), and interim visit data showed that this was significant at weeks 0-4 (P =.03 Dysport-240 vs placebo). The mean duration of headache during weeks 0-4 was lower with Dysport-240 (P =.04 vs placebo). Improvements in patient and investigator global assessments of change between weeks 0-4 and 8-12 were significant for the Dysport-240 group (both P <.05 vs placebo). Conclusions.-Limitations in study design and assessment tools employed may have contributed to the inconclusive nature of the primary end point data. Dysport-240 showed significant benefit over placebo at some end points and further trials with more appropriate outcome measures are required to evaluate effectively this treatment. © 2010 American Headache Society.